Esthetically objectionable fluorosis attributable to water fluoridation - Griffin SO, Beltra´n ED, Lockwood SA, Barker LK. (Blackwell Synergy, 2002)
We compared estimates of fluorosis prevalence and risk attributable to fluoridation using an index applied to the entire dentition and to the maxillary anterior teeth. We also estimated the prevalence of perceived esthetic problems attributable to current fluoridation policy (Attributable Burden).